XXI Century Education and its contribution to the employment rate of romanian labour market - Şerb Diana Elena; Cicioc Nicoleta Camelia (Computational Methods in Social Sciences, 2015)
The reason for choosing this theme is that the employers show a lack of interest in the workforce that has benefited from the educational process, a lack of interest which begun to intensify lately, educational process meaning formal education, namely that obtained in universities. The development in the modern society in terms of information and communication technology makes employers modify their preferences. If up to the intensification of the financial crisis the university graduates were the ones being employed, now less educated people are sought. The central idea of the article is that young people show a skeptical attitude on further education after high school, and the fact that they do not want to surpass themselves and not focus on lifelong learning, poses a threat to society, an education that does not end once the individual no longer has the status of pupil or student. To support the argument over the scientific approach, we’re using linear regression, experiments, and opinion surveys using a questionnaire. The importance of this scientific endeavor is that it is a warning for the entrepreneurs, emphasizing the fact that labor resources with limited knowledge cannot perform tasks at the work place, practically do not perform well, and this is reflected in the company's financial data.